Biosynthesis of anti-proliferative gold using endophytic fusarium oxysporum strain isolated from neem (A-indica) leaves - Siddiqui, Ejaz Ahmad; Ahmad, Absar; Julius, Anju; Syed, Asad; Khan, Shadab; Kharat, Mahesh; Pai, Kalpana; Kadoo, Narendra Y.; Gupta, Vidya (Current topics in medicinal chemistry, 2016)
Here we report a simple, rapid, environment friendly approach for the synthesis of gold nanoparticles using neem (Azadirachta indica A. Juss.) fungal endophyte, which based upon morphological and cultural characteristics was eventually identified as Fusarium oxysporum. The aqueous precursor (HAuCl4) solution when reacted with endophytic fungus resulted in the biosynthesis of abundant amounts of well dispersed gold nanoparticles of 10-40 nm with an average size of 22nm. These biosynthesized gold nanoparticles were then characterized by standard analytical techniques such as UV-Visible spectroscopy, X-ray diffraction, Transmission Electron Microscopy and Fourier Transform Infrared Spectroscopy. Cytotoxic activity of these nanoparticles was checked against three different cell types including breast cancer (ZR-75-1), Daudi (Human Burkitt's lymphoma cancer) and normal human peripheral blood mononuclear cells (PBMC), where it was found that our gold nanoparticles are anti-proliferative against cancer cells but completely safe toward normal cells. In addition to this, assessment of toxicity toward human RBC revealed less than 0.1 % hemolysis as compared to Triton X-100 suggesting safe nature of our biosynthesized gold nanoparticles on human cells. Also, our nanoparticles exhibited no anti-fungal (against Aspergillus niger) or anti-bacterial [against Gram positive (Bacillus subtilis & Staphylococcus aureus) and Gram negative (Escherichia coli & Pseudomonas aeruginosa) bacteria] activity thus suggesting their non-toxic, biocompatible nature. The present investigation opens up avenues for eco-friendly, biocompatible nanomaterials to be used in a wide variety of application such as drug delivery, therapeutics, theranostics and so on.

Biosynthesis of fluorescent Bi2S3 nanoparticles and their application as dual-functionSPECT-CT probe for animal imaging - Uddin, Imran; Ahmad, Absar; Siddiqui, Ejaz Ahmad; Rahaman, Sk. Hasanur; Gambhir, Sanjay (Current Topics In Medicinal Chemistry, 2016)
Bismuth sulphide (Bi2S3) is an excellent semiconductor and its nanoparticles have numerous significant applications including photovoltaic materials, photodiode arrays, bio-imaging, etc. Nevertheless, these nanoparticles when fabricated by chemical and physical routes tend to easily aggregate in colloidal solutions, are eco-unfriendly, cumbrous and very broad in size distribution. The aim of the present manuscript was to ecologically fabricate water dispersible, safe and stable Bi2S3 nanoparticles such that these may find use in animal imaging, diagnostics, cell labeling and other biomedical applications. Herein, we for the first time have biosynthesized highly fluorescent, natural protein capped Bi2S3 nanoparticles by subjecting the fungus Fusarium oxysporum to bismuth nitrate pentahydrate [Bi(NO3)(3).5H(2)O] alongwith sodium sulphite (Na2SO3) as precursor salts under ambient conditions of temperature, pressure and pH. The nanoparticles were completely characterized using recognized standard techniques. These natural protein capped Bi2S3 nanoparticles are quasi-spherical in shape with an average particle size of 15 nm, maintain long term stability and show semiconductor behavior having blue shift with a band gap of 3.04 eV. Semiconductor nanocrystals are fundamentally much more fluorescent than the toxic fluorescent chemical compounds (fluorophores) which are presently largely employed in imaging, immunohistochemistry, biochemistry, etc. Biologically fabricated fluorescent nanoparticles may replace organic fluorophores and aid in rapid development of biomedical nanotechnology. Thus, biodistribution study of the so-formed Bi2S3 nanoparticles in male Sprague Dawley rats was done by radiolabelling with Technitium-99m (Tc-99m) and clearance time from blood was calculated. The nanoparticles were then employed in SPECT-CT probe for animal imaging where these imparted iodine equivalent contrast.